Feeling anxious: a twin study of panic/somatic ratings, anxiety sensitivity and heartbeat perception in children. - Eley, T; Gregory, A; Clark, D; Ehlers, A (2007)
BACKGROUND: Little is known about mechanisms of genetic influence on panic, particularly in childhood. Cognitive theories of panic disorder highlight threatening interpretations of physical sensations, and increased awareness of such sensations. Specifically, anxiety sensitivity (AS) and heartbeat perception (HBP) have been associated with panic in adults and children. We examined genetic and environmental influences on childhood AS, HBP, panic/somatic ratings, and their associations. METHODS: Self-ratings of AS and DSM-based anxiety (including panic/somatic items) were obtained from 300 eight-year-old twin pairs (600 individuals), selected for mother-rated child anxiety at age 7. HBP was also assessed. RESULTS: Panic/somatic ratings were significantly correlated with both AS (r = .55) and continuous HBP error scores (r = -.13). AS and HBP scores showed significantly greater correlations with panic/somatic ratings than with all other anxiety scales, except for HBP and school anxiety. Genetic influences on panic/somatic ratings were modest (15%), and moderate for both AS (37%), and HBP (30%). Non-shared environmental influences were substantial. The genetic correlations between panic/somatic ratings and both AS and HBP error scores were .98 (95% CI: .74-1.00) and -.46 (95% CI: -1.00-1.00) respectively. CONCLUSIONS: Self-ratings of panic and AS overlap genetically. Future research should consider whether AS mediates genetic risk for panic disorder.